POLITICS OF GM CROPS IN INDIA public policy discourse. - Navneet, Asheesh ([S.l.] : ROUTLEDGE INDIA, 2020)
This book discusses the conflicting discourse around GM crops in India. It brings together concerns related to food production, farming, environment, health, ownership and policymaking on the use of genetically modified crops in India. The volume analyses apprehensions around GM technology from the perspective of the various stakeholders involved in the debate. Through field surveys and interviews with scientists, economists, environmentalists, civil society activists as well as cotton growing farmers from the states of Telangana and Maharashtra, it highlights the vulnerabilities and questions related to the short-term and long term impacts of using GM technology on farmers, food production, health, the agricultural economy and the environment. The book proposes ways for the use of GM technology which takes stock of economic and farming limitations and accordingly brings in reforms and policies to reconcile the conflicting arguments of stakeholders. This volume will be of great interest to researchers and students of development studies, political science, sociology, agricultural studies and sciences and biotechnology. It will also be useful for policymakers, think tanks and NGOs working with farmers or agriculture collectives on policy issues.
OCLC-licensed vendor bibliographic record.
Keywords: Transgenic plants -- Political aspects -- India; Agriculture and state -- India; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Globalization